Experimental Modelling of Gripper Arm Using CAD Fusion 360 and Fused Deposition Modelling 3D Printing Process of Polymer - Nur, Nurhidayanti; Ishak, Ishak; Bayu Wicaksono, Ariawan (Politeknik Bosowa, 2024)
The use of Fusion 360 CAD technology and Fused Deposition Modelling (FDM) 3D printing process enables the development of complex and efficient gripper arm designs. This study explores the effect of mesh and infill density parameters on the print time, weight, and strength of parts printed using ABS material. The results show that a 40% mesh with 40% infill is optimal for lightweight applications due to material and time efficiency. In contrast, a 60% mesh with 80% infill is more suitable for heavy loads due to higher strength. With this design approach, components that meet the needs of robotics-based industries are produced, reinforcing the contribution of FDM technology in modern manufacturing.